Challenges and opportunities to improve autism services in low-income countries: lessons from a situational analysis in Ethiopia. (1st July 2016) - Tekola, B.; Baheretibeb, Y.; Roth, I.; Tilahun, D.; Fekadu, A.; Hanlon, C.; Hoekstra, R. A.
Abstract : Background: Little has been reported about service provision for children with autism in low-income countries. This study explored the current service provision for children with autism and their families in Ethiopia, the existing challenges and urgent needs, and stakeholders' views on the best approaches to further develop services. Methods: A situational analysis was conducted based on (i) qualitative interviews with existing service providers; (ii) consultation with a wider group of stakeholders through two stakeholder workshops; and (iii) information available in the public domain. Findings were triangulated where possible. Results: Existing diagnostic and educational services for children with autism are scarce and largely confined to Ethiopia's capital city, with little provision in rural areas. Families of children with autism experience practical and psychosocial challenges, including severe stigma. Informants further raised the lack of culturally and contextually appropriate autism instruments as an important problem to be addressed. The study informants and local stakeholders provided several approaches for future service provision expansion, including service decentralisation, mental health training and awareness raising initiatives. Conclusions: Services for children with autism in Ethiopia are extremely limited; appropriate care for these children is further impeded by stigma and lack of awareness. Ethiopia's plans to scale up mental healthcare integrated into primary care provide an opportunity to expand services for children with autism and other developmental disorders. These plans, together with the additional strategies outlined in this paper can help to address the current service provision gaps and may also inform service enhancement approaches in other low-income countries.